1996
DOI: 10.1177/105477389600500307
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Elders Speak out

Abstract: The purpose of the study was to describe the experience of some Chinese elders who are living with, and dependent on, their adult children. A second purpose was to explore the potential physical and mental health outcomes associated with being dependent on their adult children for psychological, financial, social, and, in some cases, physical care and support. The sample consisted of 10 first-generation Chinese elderly. Taped interviews were carried out with the assistance of an interpreter using semistructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Ishii-Kuntz (1997) and Kamo and Zhou (1994) suggest that this traditional family value continues even when people migrate to a new society where family relationships and living arrangements are different. In contrast, some studies (Lam, Pacala, & Smith, 1997;MacKinnon, Gien, & Durst, 1996) report that elderly immigrants experience less family support from their adult children and perceive this as a major stressor in their lives. The family relationship may be a key factor to understanding depression among elderly Korean immigrants, and there is a lack of studies that explore the impact of family relationships of Korean immigrants on depression.…”
mentioning
confidence: 74%
“…Ishii-Kuntz (1997) and Kamo and Zhou (1994) suggest that this traditional family value continues even when people migrate to a new society where family relationships and living arrangements are different. In contrast, some studies (Lam, Pacala, & Smith, 1997;MacKinnon, Gien, & Durst, 1996) report that elderly immigrants experience less family support from their adult children and perceive this as a major stressor in their lives. The family relationship may be a key factor to understanding depression among elderly Korean immigrants, and there is a lack of studies that explore the impact of family relationships of Korean immigrants on depression.…”
mentioning
confidence: 74%
“…In one of these studies (Gannagé 1999), five interpreters were used in the interviews but gender was only mentioned for three of them. In another study (Mackinnon et al. 1996), the only information about the interpreters’ background was ‘young’ and was found under the heading ‘Findings and Discussion’.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Somerville (2001), the interpreter was not known to any of the interviewees. Finally, in more than half of the papers, nothing at all was said about the competence of the interpreter(s) (Kulig 1995, Mackinnon et al. 1996, Norman 1996, Essén et al.…”
Section: Resultsmentioning
confidence: 99%
“…This was a difficult emotional issue for the immigrant elders who still cherished family solidarity. In addition, those elderly immigrants who relied heavily on their adult children experienced more stress than those who were not dependent [10]. Another pilot study conducted by Lee [11] reported that the majority of elderly Korean immigrants felt a strong sense of shame, failure, powerlessness, and embarrassment because of their heavy dependence on their adult children.…”
Section: Introductionmentioning
confidence: 99%